Fuzzy Performance Measurement: A Literature Review - Oztaysi, Basar; CevikOnar, Sezi; Cebi, Selcuk; Kahraman, Cengiz (SPRINGER INTERNATIONAL PUBLISHING AG, 2024)
Performance measurement (PM) is essential for assessing organizational efficacy, employing various methodologies and frameworks. In the literature, performance measurement is handled from two perspectives in the first group, effects of performance and factors affecting the organizational performance is analyzed. The second group focus on quantitative analysis which focus on tools and techniques which can be used in performance measurement. This paper examines the utilization of fuzzy sets in performance measurement studies, drawing from a literature survey conducted on Scopus. The analysis reveals a predominant use of ordinary fuzzy sets, with some studies employing extensions such as type-2 fuzzy sets and intuitionistic fuzzy sets. Furthermore, the paper delves into the methodologies employed in fuzzy performance measurement, highlighting Analytic Hierarchy Process and Data Envelopment Analysis as prominent approaches. By synthesizing these findings, the paper contributes to understanding the landscape of fuzzy-based performance measurement and underscores its significance in contemporary management practices.
Keywords: Performance Measurement; Fuzzy Sets; multi-criteria decision making; Computer Science